Implementasi Pendidikan Karakter Harun Al Rashid di Mahad Ummul Quro Riau - Yopi Ardila; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
This study examines the implementation of character education based on Islamic educational values developed during the reign of Caliph Harun al-Rashid through a case study at Ma’had Ummul Quro Riau, as an effort to reactualize the legacy of classical Islamic education in responding to contemporary educational challenges. The research focuses on analyzing how the concept of character education that emerged in the Abbasid era—emphasizing the integration of revelation and reason, knowledge and adab, as well as spirituality and rationality—is contextually applied within the institutional practices of the ma’had. The study aims to reconstruct the epistemological and axiological foundations of Islamic education during the era of Harun al-Rashid while examining their relevance to student character formation amid moral crises and value disorientation in modern educational systems. This research employs a qualitative method using a case study approach, combined with a historical-philosophical framework and contextual analysis. The case study design was selected to achieve an in-depth and holistic understanding of the internalization of character education values within Ma’had Ummul Quro Riau as a dynamic Islamic educational institution. Data were collected through analyses of classical and contemporary literature on Abbasid-era Islamic educational thought, observations of educational practices at the ma’had, and institutional document analysis related to curriculum design, adab development, and students’ spiritual activities. Data analysis was conducted thematically by linking classical Islamic educational values—particularly the concept of ta’dīb, the integration of knowledge and faith, and the moral-spiritual orientation of knowledge—with the realities of modern educational implementation within the case study context. The findings indicate that Islamic education during the era of Harun al-Rashid functioned not merely as a means of knowledge transmission but as an instrument for forming morally cultivated individuals (insān adabī), positioning knowledge as a pathway toward moral and spiritual refinement. These values are implemented at Ma’had Ummul Quro Riau through an integrative curriculum combining religious and general sciences, character development grounded in adab within academic and social life, the reinforcement of spiritual discipline, and the cultivation of tawhidic consciousness as the foundation of all educational activities. These findings demonstrate a substantive continuity between the classical Islamic educational paradigm of the Abbasid era and contemporary Islamic educational practices within the ma’had.